2014
DOI: 10.1002/pip.2540
|View full text |Cite
|
Sign up to set email alerts
|

Life‐cycle greenhouse gas emissions and energy payback time of current and prospective silicon heterojunction solar cell designs

Abstract: Silicon heterojunction (SHJ) cells offer high efficiencies and several advantages in the production process compared to conventional crystalline silicon solar cells. We performed a life-cycle assessment to identify the greenhouse gas (GHG) footprint, energy payback time (EPBT) and cumulative energy demand of four different SHJ solar cell designs. We analyse these environmental impacts for cell processing and complete systems for both current and prospective designs. On the basis of in-plane irradiation of 1700… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 20 publications
0
43
0
1
Order By: Relevance
“…For those developing countries whose energy access promotions have not met the requirement of sustainable development [52], the results of this study indicate that solar-powered recycling may be beneficial from an energy perspective in the future. In addition, solar-powered recycling can help developing countries to reduce carbon emissions, which is necessary because the carbon emissions from developing countries are greater than from developed countries with the same unit of value-added [53].…”
Section: Applications For Developing Countriesmentioning
confidence: 87%
“…For those developing countries whose energy access promotions have not met the requirement of sustainable development [52], the results of this study indicate that solar-powered recycling may be beneficial from an energy perspective in the future. In addition, solar-powered recycling can help developing countries to reduce carbon emissions, which is necessary because the carbon emissions from developing countries are greater than from developed countries with the same unit of value-added [53].…”
Section: Applications For Developing Countriesmentioning
confidence: 87%
“…Ex-ante or prospective LCA studies have shown that emerging technologies can benefit from better design choices and efficient industrial processes [34,35]. Furthermore, the environmental performance of technologies can benefit from economies of scale.…”
Section: Future Perspectivementioning
confidence: 99%
“…The key parameters for wafer based crystalline silicon technologies are subject to prospective future scenarios based on expected future trends. A similar modelling approach was applied in Louwen et al [4], Frischknecht et al [29], and Rufer and Braunschweig [30]. These key parameters were modelled based on future projections in the International Technology Roadmap for Photovoltaics (ITRPV) for mono-Si single-junction solar cells [41], in Burschka et al [42], and in Yang et al [43] for non-bifacial perovskite single-junction cells and in Werner [10], Albrecht et al [18], Bush et al [9], and Almansouri et al [26] for monolithic 2-two terminal SHJ-PSC tandem cells.…”
Section: Prospective Scenarios and Model Approachmentioning
confidence: 99%
“…The LCI of the deposition of the amorphous silicon layers for the monolithic SHJ-PSC tandem cell are based on Louwen et al [4]. The LCI data of cell and module production are based on the LCI data for mono-Si cells and modules (panels) available in the IEA PVPS LCI report [31].…”
Section: Life Cycle Inventorymentioning
confidence: 99%
See 1 more Smart Citation